2018
DOI: 10.1029/2018gl078604
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Driver of Energetic Electron Precipitation Using Coordinated Multisatellite Measurements

Abstract: Magnetospheric plasma waves play a significant role in ring current and radiation belt dynamics, leading to pitch angle scattering loss and/or stochastic acceleration of the particles. During a non‐storm time dropout event on 24 September 2013, intense electromagnetic ion cyclotron (EMIC) waves were detected by Van Allen Probe A (Radiation Belt Storm Probes‐A). We quantitatively analyze a conjunction event when Van Allen Probe A was located approximately along the same magnetic field line as MetOp‐01, which de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 63 publications
2
46
0
Order By: Relevance
“…While precipitating protons can produce proton aurora Yuan et al, 2010),~MeV electrons can interact with atmospheric nitrogen and hydrogen oxides, leading to ozone reduction (e.g., Meraner & Schmidt, 2018). The efficacy of EMIC waves in scattering MeV electrons and ring current protons has been confirmed in multiple studies, both observationally and theoretically (Blum et al, 2015;Capannolo et al, 2018Capannolo et al, , 2019Hirai et al, 2018;Qin et al, 2018Qin et al, , 2019Shekhar et al, 2017;Woodger et al, 2018;Yuan et al, 2018). However, the techniques and the satellites used have limitations that still leave a few open questions, for example, on the minimum energy of electrons (E min ) that can be scattered into the loss cone.…”
Section: 1029/2019gl084202mentioning
confidence: 97%
“…While precipitating protons can produce proton aurora Yuan et al, 2010),~MeV electrons can interact with atmospheric nitrogen and hydrogen oxides, leading to ozone reduction (e.g., Meraner & Schmidt, 2018). The efficacy of EMIC waves in scattering MeV electrons and ring current protons has been confirmed in multiple studies, both observationally and theoretically (Blum et al, 2015;Capannolo et al, 2018Capannolo et al, , 2019Hirai et al, 2018;Qin et al, 2018Qin et al, , 2019Shekhar et al, 2017;Woodger et al, 2018;Yuan et al, 2018). However, the techniques and the satellites used have limitations that still leave a few open questions, for example, on the minimum energy of electrons (E min ) that can be scattered into the loss cone.…”
Section: 1029/2019gl084202mentioning
confidence: 97%
“…In addition, in the presence of sufficiently narrow cold plasma structure, the precipitation regions of radiation belt electrons related to different wave modes should nearly coincide so that it is difficult to attribute precipitation of radiation belt electrons only to EMIC waves (Yahnin et al, ). Recently, some studies have focused on the link between EMIC waves observed by the inner magnetospheric satellites and the precipitation of radiation belt electrons detected by the ionospheric satellite or inferred from the ground‐based observations (e.g., Blum et al, ; Capannolo et al, ; Li et al, ; Qin et al, ; Rodger et al, ; Usanova et al, ; J. Zhang, Halford, et al, ). However, the precipitations of >MeV radiation belt electrons always coincided with the precipitations of <MeV RC electrons, implying it difficult to attribute precipitation of radiation belt electrons only to EMIC waves.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have focused on the link between EMIC waves observed by the inner magnetospheric satellites and the precipitation of radiation belt electrons detected by the ionospheric satellite or inferred from the ground-based observations (e.g., Blum et al, 2015;Capannolo et al, 2018;Li et al, 2014;Qin et al, 2018;Rodger et al, 2015;Usanova et al, 2014;J. Zhang, Halford, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…During the conjugate observations between Van Allen Probes and POES, significant and sporadic increases of precipitating (field‐aligned) electron fluxes measured by POES can be seen in Figure c after 11:02 UT in the ≈300‐ to 700‐keV energy range, sometimes reaching the level of the trapped fluxes (at 90°). Such sub‐MeV electrons could have been affected by resonant wave‐particle interactions and precipitated into the atmosphere, possibly by the combined effects of EMIC and ULF waves (see similar observations from Capannolo et al, ). Simultaneously with EMIC wave observations, some decrease of field‐aligned electron (0.5–1.5 MeV) fluxes was observed by the Van Allen Probes near the equator (not shown): It could also be due to a precipitation induced by EMIC waves (e.g., see Usanova et al, ; Wang et al, ).…”
Section: Selected Observations Of Relativistic Electron Loss In the Pmentioning
confidence: 75%